Lithic Raw Materials of the Late Palaeolithic/Neolithic Industries in Jabal Nefusa, Tripolitania - Mrazek, Ivan; Svoboda, JIŘÍ (Anthropologie, 1986)
The mineralogic-petrographical character of the raw materials of the Late Palaeolithic/Neolithic stone industries, collected at several open air-sites in the area of Jabal Nefusa, have been studied and the origin of the raw materials have been recognized. Two types of Upper Cretaceous (Nalut Formation) cherts (the coloured and the striped ones), used for the manufacture of implements, have been distinguished. They may be considered either local or short-distance imported raw materials.
Keywords: Géologie -- Djebel Nefousa

Stratigraphic studies on Quaternary floodplain deposits of the Eastern Gefara Plain. S.P.L.A.J. - Anketell, J. M.; Ghellali, S. M. (Libyan Studies, 1983)
Abstract The Quaternary deposits of the Gefara Plain are comprised of three major facies – alluvial fan facies of sands and gravels which blankets the base of the Jebel Nafusa escarpment; floodplain facies of fluvial sands and silts with aeolian dunes which underlies most of the Gefara Plain and, aeolian coastal dune facies, predominantly calcarenitic, which is confined to a narrow coastal zone. Well exposed sections in the eastern part of the plain allow sub-division of the floodplain deposits into a number of mappable units defined and bounded by surfaces of stratigraphic discontinuity. The lithologies of these units are described and compared from selected type sections. The relationships between the units, their geometry, and the nature of the surfaces of stratigraphic discontinuity are discussed. It is proposed that, the lithostratigraphic sequence displayed by the Quaternary floodplain deposits of the eastern Gefara region provides a firm basis for correlation, not only with floodplain deposits in other parts of the plain but also with the other major facies developed in the area. In addition, the recognition of significant stratigraphic breaks in the sedimentary sequence combined with facies analysis lays a firm foundation for an interpretation of the geological history of the region.
Keywords: Géologie -- Djebel Nefousa

Quaternary Deposits of Northern Libya — Lithostratigraphy and Correlation - Anketell, J. M. (Libyan Studies, 1989)
In recent years basic regional geological mapping of northern Libya by the Industrial Research Centre, Tripoli, together with the UNESCO Libyan Valleys Survey of eastern Tripolitania and the work of the author and Dr S. M. Ghellali in the Jifarah Plain and Jabal Nafusah, have greatly added to our knowledge of Quaternary deposits in the region. This work is described and evaluated against the background of earlier studies. The succession of major depositional, soil forming and erosional events which characterise the fluvio-aeolian deposits of the Jifarah Formation can be recognised in, and thus used to subdivide, laterally equivalent aeolianite, fangravel and wadi gravel deposits in the Jifarah Plain. Comparisons of this succession with others from throughout the region indicate that the events are of regional significance and that the Jifarah sequence provides a sound framework for lithostratigraphic correlation and a basis for facies analysis and chronostratigraphic studies. This review is largely limited to the northern margins of Libya north of the 30th parallel (Fig. 1). It is convenient to subdivide the zone into several regions. These are: (a) The Jifarah Plain and foothills of the Jabal Nafusah. (b) The Hammada Al Hamra Plateau and major valleys of eastern Tripolitania. (c) The coastal region from Misratah to Ajdabiyah. (d) Cyrenaica from Soluq to Al Bardia.
Keywords: Géologie -- Djebel Nefousa

Depositional environments of the Chicla, Cabao and Chameau Mort Formations as revealed by scanning electron microcopy - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie -- Djebel Nefousa

Water resources of the Socialist People's Libyan Arab Jamahiriya - Pallas, D. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie -- Djebel Nefousa

Structural control of groundwater flow in the Mesozoic sandstone aquifers of the eastern part of Jabal Nafusah, Libya. - Singh, G. D. S. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie -- Djebel Nefousa

Stratigraphy and lithofacies of the continental clastics (Upper Jurassic and Lower Cretaceous) of Jabal Nafusah, NW Libya. - El-Zouki, A. Y. (The geology of Libya. Volume II. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978, 1980)
Keywords: Géologie -- Djebel Nefousa

Stratigraphic nomenclature of the pre-Upper Cretaceous Mesozoic rocks of Jabal Nafusah, NW Libya. - Fatmi, A. N.; Eliagoubi, B. A.; Hammuda, O. S. (The geology of Libya. Volume I. Second Symposium on the Geology of Libya, held at Tripoli, September 16-21, 1978., 1980)
Keywords: Géologie -- Djebel Nefousa

Mineralogical composition of Jabal Nafusah phonolites - Bausch, W. M. (Academic Press, 1980)
The Jabal Nafusah phonolites are characterized by the dominance of felsic components, or a very low colour ratio. As mentioned by Almond et al. (1974), phenocrysts (mostly of alkali feldspar) may occur, but generally the phonolites are fine grained, poorly crystallized or even aphyric. Along with microscope analysis, the mineralogical composition has been investigated, essentially by means of X-ray diffraction. The chief (felsic) components found were: sanidine, analcime, nepheline, sodalite and albite (given in order of approximately decreasing frequency). The frequency of analcime is quite remarkable, and has not been hitherto described. Also shown are the relations of changing proportions of mineralogical compositions and detailed X-ray data.
Keywords: Géologie -- Djebel Nefousa